2014 IEEE International Conference on Robotics and Automation (ICRA) 2014
DOI: 10.1109/icra.2014.6907527
|View full text |Cite
|
Sign up to set email alerts
|

Detection of slippery terrain with a heterogeneous team of legged robots

Abstract: Abstract-Legged robots come in a range of sizes and capabilities. By combining these robots into heterogeneous teams, joint locomotion and perception tasks can be achieved by utilizing the diversified features of each robot. In this work we present a framework for using a heterogeneous team of legged robots to detect slippery terrain. StarlETH, a large and highly capable quadruped uses the VelociRoACH as a novel remote probe to detect regions of slippery terrain. StarlETH localizes the team using internal stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Heterogeneous multi-agent collaboration tasks leverage the diverse capabilities and complementary attributes of the robots to enhance the scalability and robustness of the multi-agent system. There are already some heterogeneous robot combinations proposed such as aerial-ground collaboration [21,53], main-picket collaboration [13], and humanoid-quadruped collaboration [43]. However, challenges in coordination, planning, and execution are also presented.…”
Section: A Heterogeneous Multi-agent Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous multi-agent collaboration tasks leverage the diverse capabilities and complementary attributes of the robots to enhance the scalability and robustness of the multi-agent system. There are already some heterogeneous robot combinations proposed such as aerial-ground collaboration [21,53], main-picket collaboration [13], and humanoid-quadruped collaboration [43]. However, challenges in coordination, planning, and execution are also presented.…”
Section: A Heterogeneous Multi-agent Tasksmentioning
confidence: 99%
“…Decentralized cooperative transportation by aerial and ground robots equipped with manipulators is discussed in [21]. Haldane et al [13] undertake joint locomotion and perception tasks by legged robots of varying sizes and capabilities. There is also work dealing with multi-task collaboration scenarios involving a variety of heterogeneous robots and humans [25].…”
Section: A Heterogeneous Multi-agent Tasksmentioning
confidence: 99%
“…A lower value corresponds with more efficient locomotion. Specific resistance as defined, for example, in Zarrouk et al [18] is shown in (2).…”
Section: B Specific Resistance and Drag Energymentioning
confidence: 99%
“…Recently developed low-cost folded legged millirobots have demonstrated high-speed locomotion [1] and turning maneuverability on diverse terrain [2] [3], which makes them potential candidates for performing a swarm-like distributed search for survivors in disaster scenarios such as an earthquake building collapse. This class of palm-sized robots is manufactured using the scaled Smart Composite Microstructures (SCM) process, which enables inexpensive and rapid fabrication of millimeter-scale integrated folded mechanisms that drive many legs with few motors [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…9,10) Therefore, hexapods can realize stable walking with simple control. There are many successful applications for hexapod robots that realize robust movement on various terrains with high stability, such as HAMR, 4,11,12) RoACH, 13) VelociRoACH, [14][15][16][17] DASH, 18) Rhex, [19][20][21] and iSprawl. 22,23) Swarm algorithms for micro robots are more desirable than fewer normal sized robots in terms of efficiency and costs.…”
Section: Introductionmentioning
confidence: 99%